High acid resistant SiOC ceramic membranes for wastewater treatment - Guo, Fangwei; Su, Dong; Liu, Yang; Wang, Jianming; Yan, Xiao; Chen, Jing; Chen, Shunquan (Ceramics international, 2018)
Tailoring the pore structures of ceramic membranes is the essential challenge in its application for wastewater treatment. In this paper, silicon oxycarbide (SiOC) ceramic membranes with tunable pore structures are fabricated by coating polysiloxanes (PSO) onto YSZ hollow fiber membranes followed with subsequent pyrolysis. The SiOC ceramics, with a pore size in the range of 50 nm-2 µm and porosity of 35–40%, have been obtained by varying the pore forming agents. Moreover, the SiOC layers endow the fiber membranes with high corrosion resistance regarding merely 0.07 wt% weight loss in 20 wt% H2SO4 solution, since that the unique silicon oxycarbide microlattice structures can provide remarkable chemical durability. Together with considerable mechanical strength and pure water permeate flux, such SiOC ceramic membranes should find applications in industrial wastewater treatment.